Source method biases as implicit personality theory at the domain and facet levels - McCrae, Robert R; Mõttus, René; Hřebíčková, Martina; Realo, Anu; Allik, Jüri (Journal of personality, 2019)
OBJECTIVE: We tested predictions about the structure and magnitude of method biases in single-source personality trait assessments. We expected a large number of distinct biases that would parallel the observed structure of traits, at both facet and item levels. METHOD: We analyzed multimethod ratings on the Estonian NEO Personality Inventory-3 in a sample of 3,214 adults. By subtracting informant ratings from self-reports, we eliminated true score variance and analyzed the size and structure of the residual method biases. We replicated analyses using data (N = 709) from the Czech Revised NEO Personality Inventory. RESULTS: The magnitude of method biases was consistent with predictions by McCrae (2018, Psychological Assessment). Factor analyses at the facet level showed a clear replication of the normative Five-Factor Model structure in both samples. Item factor analyses within domains showed that facet-level method biases mimicked the facet structure of the instrument. CONCLUSIONS: Method biases apparently reflect implicit personality theory (IPT)-beliefs about how traits and trait indicators covary. We discuss the (collective) accuracy and possible origins of IPT. Because method biases limit the accuracy of single-source assessments, we recommend assessments that combine information from two or more informants.
Keywords: multimethod assessment; dospělí; Personality Assessment; Female; measurement error; Personality; srovnání kultur; Adult; ženské pohlaví; mladý dospělý; Estonsko; cross-cultural; Adolescent; lidé; testování osobnosti; Self Report; osobnost; Aged, 80 and over; psychologická teorie; Humans; Personality Inventory; personality structure; Male; Aged; Czech Republic; Young Adult; Cross-Cultural Comparison; Psychological Theory; Česká republika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; osobnostní dotazník; zpráva o sobě; Middle Aged; mladiství; Estonia